KOMBINASI EKSTRAK SECANG (CESALPINIA SAPPAN L.) DAN METFORMIN SEBAGAI ANTI HIPERGLIKEMIA SECARA IN VIVO - Cikra Ikhda Nur Hamidah Safitri; Putri Ade Muhaimatus Solikhah (Jurnal Insan Farmasi Indonesia, 2025)
Secang wood (Caesalpinia sappan L.) is considered one of the sources of modern medicine that may have effective hypoglycemic effects, or lowering blood sugar. This wood is rich in various phytochemicals. The aim of this study is to observe how the combination of secang bark extract and metformin acts as an antihyperglycemic in male rats. This research is an experimental study. The doses used include Secang wood extract of 285.71 mg/kg and 666.66 mg/kg, Metformin 300 mg/kg, and a combination of both in a ratio of 1:1. The test animals were divided into seven groups (each consisting of five individuals). Diabetes induction was performed using alloxan. Blood glucose levels were measured at baseline, on days 1, 3, 7, 14, and 21 after treatment. Data were analyzed using ANOVA. The results showed that the combination therapy provided a synergistic effect, marked by a highly significant decrease in blood glucose levels (p < 0.01) starting from day one, and the glucose levels returned to normal on day 21 after treatment. The administration of Secang wood extract alone has antihyperglycemic potential, and when combined with metformin, it produces a significant hypoglycemic effect.